Experimental study and signal analysis of acoustic emission from power MOSFET. (December 2021) - Zou, Xiang; He, Yunze; Zhang, Zhenjun; Li, Mengchuan; She, Saibo; Geng, Xuefeng; Bai, Yun; Dang, Xiangzhao; Ren, Dantong; Chen, Zhiyu
Abstract: The traditional condition monitoring (CM) method of power electronic device detection is built based on electrical, magnetic, and thermal parameters, respectively. In this paper, a novel potential method based on acoustic or stress parameter is proposed. The mechanical stress wave (MSW) and electromagnetic wave (EMW) generated from power metal-oxide-semiconductor field-effect transistor (MOSFET) are analyzed under low voltage condition for the first time. Then, the testing system is set up based on acoustic emission (AE), and corresponding experiments are conducted to verify the correctness of the primary theory. In the experiment, AE signals generated by power MOSFET under pulse excitation can be divided into low-frequency and high-frequency components with the boundary of 300 kHz. The relationship between low-frequency components and gate-source voltage ( V gs ) is approximately linear and the high-frequency components contain two reverse pulse waves which is nearly a linear quantitative relationship between the positive one and the drain-source voltage ( V ds ). AE sensor is coupled in two different ways, which are used to verify that the high-frequency components are mainly EMW generated at the moments of turn-on and turn-off. In addition, the low-frequency components are mainly MSW signal. This research provides a new idea and method for the condition CM of power MOSFET. Highlights: A unique approach is exhibited to monitoring the operation and reliability of MOSFET structures for the first time. The AE signal different components reflect different transient processes when power MOSFET is working. The linear relationships can also be determined between the electrical parameters and the AE signal characteristic parameters.